Ecological Insights into the Dynamics of Plant Biomass-Degrading Microbial Consortia. Issue 10 (October 2017) - Jiménez, Diego Javier; Dini-Andreote, Francisco; DeAngelis, Kristen M.; Singer, Steven W.; Salles, Joana Falcão; van Elsas, Jan Dirk
Abstract : Plant biomass (PB) is an important resource for biofuel production. However, the frequent lack of efficiency of PB saccharification is still an industrial bottleneck. The use of enzyme cocktails produced from PB-degrading microbial consortia (PB-dmc) is a promising approach to optimize this process. Nevertheless, the proper use and manipulation of PB-dmc depends on a sound understanding of the ecological processes and mechanisms that exist in these communities. This Opinion article provides an overview of arguments as to how spatiotemporal nutritional fluxes influence the successional dynamics and ecological interactions (synergism versus competition) between populations in PB-dmc. The themes of niche occupancy, 'sugar cheaters', minimal effective consortium, and the Black Queen Hypothesis are raised as key subjects that foster our appraisal of such systems. Here we provide a conceptual framework that describes the critical topics underpinning the ecological basis of PB-dmc, giving a solid foundation upon which further prospective experimentation can be developed. Trends: Throughout the enrichment process for the development of plant biomass-degrading microbial consortia (PB-dmc), the inoculum source and status, substrate type, temperature, and oxygen availability determine consortial richness, diversity, and structural shifts. Spatiotemporal nutritional fluxes and microbial interactions are key factors that drive the successional dynamics in the development of PB-dmc. The dynamics of microbial interactions (synergism versus competition) that occur within PB-dmc are mostly influenced by the spatiotemporal variation in nutritional resources. The ecological understanding of PB-dmc is fundamental for the development of high-efficiency synthetic consortia that can help to maximize biological plant biomass saccharification processes.